The role of HERV envelope protein in ovarian cancer - Zhang, Jianhao; Sun, Dongyu; Zhan, Yuqing; Gao, Qing; Bao, Chenxuan; Xiang, Huayuan; Shen, Yuxuan; Gao, Qianqian; Zhang, Mengyu; Wang, Jianjun; Mao, Lingxiang (Frontiers in Cell and Developmental Biology, 2025)
Human endogenous retroviruses (HERVs) are a remnant of repeated exogenous retroviral infections in human ancestors, which have been integrated into germline cells and proliferated through retrotransposition, recombination, and reinfection. Comprising approximately 8% of the human genome, HERV genes are capable of upregulating the expression of their encoded gene products in response to both endogenous and exogenous stimuli. Among HERV gene products, the envelope (env) proteins are currently extensively investigated for their pathogenic properties in cancer. Given that HERV was initially discovered in the germline cells and the ovary is an essential female reproductive organ, this review will focus on the current knowledge of the role of HERV env protein in ovarian cancer (OC). Our review systematically delineates the expression of HERV env protein across different histological subtypes of OC and highlights its pivotal roles in tumorigenesis and cancer progression. Elucidating the role of HERV env protein in OC offers novel perspectives for developing diagnostic approaches and therapeutic monitoring strategies in OC management.